2014
DOI: 10.2460/javma.244.10.1164
|View full text |Cite
|
Sign up to set email alerts
|

Efficacy of orally administered maropitant citrate in preventing vomiting associated with hydromorphone administration in dogs

Abstract: Among the 40 study dogs, the incidence of vomiting associated with hydromorphone administration was 25%. Oral administration of maropitant prevented vomiting but not signs of nausea associated with hydromorphone administration in dogs.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
17
1

Year Published

2016
2016
2024
2024

Publication Types

Select...
4
4

Relationship

0
8

Authors

Journals

citations
Cited by 18 publications
(18 citation statements)
references
References 34 publications
0
17
1
Order By: Relevance
“…). Administration of hydromorphone IM alone induced vomiting in 25% of dogs at 0.1 mg kg −1 (Hay Kraus ) and in 87% of dogs at 0.2 mg kg −1 (Claude et al. ).…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…). Administration of hydromorphone IM alone induced vomiting in 25% of dogs at 0.1 mg kg −1 (Hay Kraus ) and in 87% of dogs at 0.2 mg kg −1 (Claude et al. ).…”
Section: Discussionmentioning
confidence: 99%
“…). Thus, the presence of vomiting after hydromorphone administration seems to vary with study conditions, duration and presence of fasting, between client‐owned and research‐bred animal populations, and according to the dose and route of the hydromorphone, and concurrent administration of other medications (Hay Kraus ).…”
Section: Discussionmentioning
confidence: 99%
“…() reported a single daily dose of maropitant to be more effective than metoclopramide administered two or three times daily in the treatment of emesis caused by various aetiologies in dogs; however, the number of PVE‐induced cases was very limited (two out of 183 cases) in that study. In other studies, maropitant was found to be effective in morphine‐ (Koh, Isaza, Xie, Cooke, & Robertson, ) or hydromorphone (Hay Kraus, )‐induced vomiting.…”
Section: Discussionmentioning
confidence: 88%
“…A subsequent study evaluated the effectiveness of the oral tablets in preventing vomiting and signs of nausea in dogs premedicated with hydromorphone. 21 Forty dogs were dosed with either placebo or maropitant citrate tablets (2.0–4.0 mg/kg) per oral (PO) 2 hours prior to hydromorphone (0.1 mg/kg) IM. Dogs were observed for vomiting and signs of nausea using the same definitions as the previous study.…”
Section: Treatment/prevention Of Perioperative Vomiting and Signs Of mentioning
confidence: 99%
“…In this study, although oral maropitant prevented vomiting, it did not prevent signs of nausea and, in fact, caused more severe signs of nausea associated with hydromorphone administration. 21 …”
Section: Treatment/prevention Of Perioperative Vomiting and Signs Of mentioning
confidence: 99%